The Assessment Profile of The Skills to Interpret Data and Evidence Scientifically in High School on The Covid-19 Virus Pandemic Content - Devi Deratama*; Ana Ratna Wulan; Sariwulan Diana; Dita Agustian (Jurnal Pendidikan Sains Indonesia, 2022)
The assessments used in learning are often not in accordance with the demands of developing students' life skills and soft skills, when in fact these skills can be the basis for students to be able to compete with the global community in the future. This research aims to analyze the assessment of the skills to interpret data and scientific evidence on the written test of virus content used in Senior High Schools (SHS). The research method is descriptive through the collection of written test questions documents. The written test questions are analyzed on the Student Worksheet, Daily Test, Mid-Semester Assessment and Final Semester Assessment. A total of six schools in the city of Bandung categorized as public and private were selected by stratified random sampling representing the quality of each school. A total of 133 virus questions from six high schools in Bandung were collected for analysis. The research instrument used a validation rubric about science epistemic skills on indicators of skills in interpreting scientific data and evidence (PISA, 2019 framework). The data were analyzed qualitatively and quantitatively with descriptive statistics. The results showed that the questions used in schools on virus content (94.75%) had not measured the skills of interpreting scientific data and evidence. These questions also do not test students’ literacy in facing a virus pandemic. Only a minor proportion of items (2.25%) were found to test data interpretation and scientific evidence skills. In general, the subject of the test in schools still focuses on memory or memorization of material, basic understanding and does not present information or data to be processed and interpreted. Most of the questions presented are only in the form of basic concepts so that it does not require students to think at high levels and reason.